Social Memory in Social and Legal Context - PELEVINA, Natalia Aleksandrovna; TILEUBERGENOV, Erazak Manapovich; UTEYEV, Bakytnur Zhumashevich; VASILIEV, Aleksei Michailovich (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
This article makes a comparison between social memory and other types of memory such as historical and social memory. Particular attention is paid to the analysis of modern memory theory in social sciences and humanities as well as basic principles and achievements in the study of social memory in Western European humanities. This topic is relevant since social memory appears as one of the forms of society and individual existence, and the focus of the human mind on the historical future suggests a constant actualization of individual and social memory layers. Social memory is an ontological need of society, the satisfaction of which provides an opportunity for society and individual to choose freely a solution method for such theoretical and practical issues as ideologization of past and present, national identity, legitimation of actions, etc. The article also analyzes the mechanisms of social memory explication and discovers the features of its functioning.